DISORDERED EATING BEHAVIOUR AND ITS ASSOCIATED FACTORS AMONG COLLEGE AND UNIVERSITY STUDENTS IN SARAWAK - Edmund, Shin Chin Vui (Universiti Malaysia Sarawak, (UNIMAS), 2020)
Introduction: Disordered eating during late adolescents and young adulthood are common in order to pursuit idealized body image. This study aims to determine the prevalence of disordered eating and its associated factors, among college and university students in Sarawak. Methodology: A cross sectional study was conducted involving 20 public and private colleges and university in Sarawak, from September 2017 to March 2020. Respondents completed self-administered questionnaire printed in English and Malay language, collecting information on sociodemographic characteristics, eating attitude, body dissatisfaction, perceived sociocultural pressure, self-esteem, drive for muscularity and perfectionism. Height and weight were recorded, to calculate body mass index. Results: A total of 652 respondents (Male: 26.5%; Female: 73.5%) aged 19 - 25 years old took part in the study. The overall prevalence of disordered eating was 25.2% (95% CI 21.9,28.7) which was higher among females (28.6% (95% CI 24.6,32.9)) than males (15.6% (95% CI 10.5,21.9)). Multivariate analysis showed female gender (OD=2.782, 95%CI: 1.653, 4.683), perfectionism (OD=1.113, 95%CI: 1.064,1.163), Christian (OD=0.226, 95%CI: 0.088,0.803), perceived sociocultural pressure (OD=1.050, 95%CI: 1.019, 1.082), and drive for muscularity (OD=1.033, 95%CI: 1.015, 1.050), were significant predictors of disordered eating. Multigroup analysis showed, perceived sociocultural pressure (β = 0.223, p < 0.001) perfectionism (β = 0.335, p < 0.01) and drive for muscularity (β = 0.266, p < 0.001) explained 25% of the variance of disordered eating in male model. While in female, perceived sociocultural pressure (β = 0.156, p < 0.001), self-esteem (β = 0.181, p < 0.01), perfectionism (β = 0.244, p < 0.001), drive for muscularity (β = 0.187, p < 0.01) and body dissatisfaction (β = 0.105, p < 0.01) explained 15 % of the variance of disordered eating. Only perfectionism was found to be significantly differ in predicting disordered eating between gender. Conclusion: The prevalence of disordered eating among college and university students in Sarawak was high. The findings suggest that there are gender differences in the factors associated with disordered eating among college and university students in Sarawak. The result of this study showed male and female may require different approach when planning disordered eating prevention programs.